Polish public opinion on the level of preparation of midwives to provide education on development of a healthy lifestyle of a pregnant woman (part II) - Iwanowicz-Palus, Grażyna; Golonka, Ewa; Bień, Agnieszka; Stadnicka, Grażyna (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Introduction. Education of a pregnant woman takes an important place in perinatal care. Midwife regardless of work place is required to promote healthy lifestyles, implement health education both because of its preventive effect on complications, obstetric complications, as well as in promoting the health of the pregnant woman and her family. Aim of the study. The aim of this study was to learn Polish public opinion on the level of preparation of midwives to provide education on development of a healthy lifestyle of a pregnant woman Material and methods. The survey was conducted between February and May 2011 on 505 respondents (293 women and 212 men) living in the eastern region (lubelskie, podkarpackie, podlaskie and świętokrzyskie). The survey was conducted using diagnostic survey method and a questionnaire technique. The research tool was the author’s questionnaire survey developed basing on a five point Likert scale. Results and conclusions. In the respondents opinion midwife is prepared to provide education about the development of healthy lifestyles of pregnant women. Lack of knowledge on the level of preparation midwife to provide education about the development of healthy lifestyles of pregnant women characterizes mainly male respondents, those aged below 20, between 21–30, with elementary education, not married, without children. Statistical analysis revealed no statistical relationship (p > 0.05) between the respondents’ opinion on the level of preparation of midwife to provide education about the development of a healthy lifestyle of a pregnant woman about work, also sport and travelling and gender, age, education, marital status and maternal experience of subjects.